Heat transfer performance with surfactants as additives - Shareen, Salwam (2014)
Technology of pipeline drag reduction has been advanced for many years. It has improved in increasing the pipeline flow potential in crude oil transportation. In the pipeline system, surfactant solutions that caused drag reduction are capable in lowering the pumping power. In this research experiment, photosensitive cinnamate group derivative compound and polymer surfactant as drag reducing agents were chosen mainly to study on the effect of photosensitive surfactant on the drag reduction and heat transfer performance and also the effect of ultraviolet light irradiation on the heat transfer and drag reduction ability of the surfactants. Water was used as the working fluid in this research and the main equipment used was Rotating Disk Apparatus. Combination of these compounds formed viscoelasticity solution. In this research experiment, rheological measurements, drag reduction and heat transfer reduction percentages were evaluated. In conclusion, these viscoelasticity solutions have a higher drag reduction percentages at higher rotational speed after ultraviolet irradiation. Lower heat transfer reduction percentages were analysed for pure photosensitive cinnamate group derivative after ultraviolet irradiation and polymer surfactant solutions hence, indicated that both solutions are good thermal conductor